The complexity of total k-domatic partition and total R-domination on graphs with weak elimination orderings. Issue 3 (2nd July 2020) - Lee, Chuan-Min
Abstract : In this paper, we propose two linear-time algorithms. One is for computing a weak elimination ordering of a bipartite distance-hereditary graph, and the other one is an alternative algorithm to solve the total R -domination problem for any chordal bipartite graph with a weak elimination ordering. Our two linear-time algorithms lead to a unified approach to several variations of total domination problems for bipartite distance-hereditary graphs. We also show that tthe total 3-domatic partition problem is NP-complete for planar graphs of maximum degree 9 and planar bipartite graphs of maximum degree 12, and show that the 4-domatic partition problem for planar graphs of maximum degree d is polynomial-time reducible to the total 4-domatic partition problem for planar graphs of maximum degree d + 1.